Startups in the Digital Era: Exploring the Role of Digital Marketing Strategy Through a Literature Review - Halim, Muhamad Abdul; Ermiani, Ermiani (CV. Strata Persada Academia, 2024)
Technological advancements in the rapidly evolving digital era have significantly transformed various sectors, including the business world. Startups focusing on technology-based solutions have become critical drivers of economic growth and disrupt traditional sectors. This study aims to bridge the gap in the literature by exploring the role of digital marketing strategies in the success of startups in the digital era. The research employs a literature review methodology, analyzing secondary data from scientific journals, books, and relevant articles. Keywords used in data collection include startups and digital marketing. The study systematically analyzes the data using content analysis to identify, classify, and analyze critical themes, patterns, and findings. Results indicate that digital marketing plays a crucial role in enhancing the maturity and performance of startups. Effective implementation of digital marketing strategies can significantly improve startups' chances of success by establishing a solid foundation in a competitive market. This research provides practical insights for startups in formulating effective and efficient marketing strategies and contributes to developing knowledge in digital marketing.